Paradigmatic Study of the Supreme Court's Downgrade Decision in the Case of Premeditated Murder of Nofriansyah Yosua Hutabarat - Zakiyah, Ninik; Corputty, Patrick; Hutabarat, Feby Amalia; Amir, Irfan; Sembiring, Adventi Ferawati (Al-Bayyinah, 2024)
This study examines the Supreme Court's decision in the premeditated murder case involving Ferdy Sambo, focusing on the reduction of the sentence from the death penalty to life imprisonment. The research aims to identify non-legal factors influencing the verdict, analyze its implications for Indonesia's criminal law paradigm, and evaluate public responses following the cassation decision. A descriptive-analytical approach was employed, utilizing legal document analysis and the post-positivist paradigm as the theoretical framework. The study interprets judicial considerations within a dynamic legal context, integrating legal norms with reflective interpretations. The findings reveal that the sentencing change reflects a shift in Indonesia's criminal law paradigm from retributive to rehabilitative, as adopted in the new Penal Code. The defendant's remorse was a key factor in the sentencing reduction. However, public response to the cassation decision indicated a decline in public trust and engagement with the judiciary, evidenced by reduced public discourse compared to the case's initial stages. The shift from retributive to rehabilitative justice served as the basis for the cassation decision. This study highlights challenges in strengthening public trust in the judicial system, emphasizing the need for greater transparency and accountability in legal decision-making processes.